Active camber system for lateral stability improvement of urban vehicles. (December 2019) - Ataei, Mansour; Tang, Chen; Khajepour, Amir; Jeon, Soo
A suspension system with the capability of cambering has an additional degree of freedom for changing camber angle to increase the maximum lateral tire force. This study investigates the effects of cambering on overall vehicle stability with emphasis on applications to urban vehicles. A full vehicle model with a reliable tire model including camber effects is employed to investigate the vehicle dynamics behavior under cambering. Besides, a linearized vehicle model is used to analytically study the effects of camber lateral forces on vehicle dynamics. Vehicle behavior for different configurations of camber angles in front and rear wheels is studied and compared. Then, an active camber system is suggested for improvement of vehicle lateral stability. Specifically, performances of active front camber, active rear camber, and their combination are investigated. The results show that a proper strategy for camber control can improve both yaw rate and sideslip angle, simultaneously. Finally, the active front camber system is compared with the well-known active front steering. It is shown that, utilizing more friction forces at the limits, active front camber is more effective in improving maneuverability and lateral stability than active front steering.